Conceptualising a Framework for Effective Performance Measurement in Cultural Precinct Development and Operation. Issue 1 (6th October 2017) - Schulz, Rebekah; Sense, Andrew; Pepper, Matthew
Abstract: The purpose of this paper is to firstly identify and synthesise critical measurement themes in extant academic literature concerning performance measurement in cultural precincts. Secondly, the paper posits for consideration a holistic and systematic framework (which embraces those themes) for developing appropriate performance measures for cultural precincts. The outcomes in this paper (a) confirm and clarify the complexity of performance measurement needed, (b) furnish a framework for practitioners embarking on the development of such measures, and (c) indicate the conceptual and pragmatic challenges faced in developing and enacting appropriate and meaningful measures for cultural precincts. Consequently, this paper serves as a conceptual positioning paper and a practical embarkation point for practitioners willing to engage with and pursue this phenomenon. Thereby, it endorses more dialogue on and further research and analysis of performance measurement in government operated cultural precincts. Abstract : This paper identifies and examines key concepts associated with appropriate and beneficial performance measurement of cultural precincts operated by government agencies. It also provides for consideration a framework for systematic and customer‐oriented performance measurement development in this context.